An anti-sortilin affibody-peptide fusion inhibits sortilin-mediated progranulin degradation - Ek, Moira; Nilvebrant, Johan; Nygren, Per-Åke; Ståhl, Stefan; Lindberg, Hanna; Löfblom, John (Frontiers in Immunology, 2024)
Heterozygous loss-of-function mutations in the GRN gene are a common cause of frontotemporal dementia. Such mutations lead to decreased plasma and cerebrospinal fluid levels of progranulin (PGRN), a neurotrophic factor with lysosomal functions. Sortilin is a negative regulator of extracellular PGRN levels and has shown promise as a therapeutic target for frontotemporal dementia, enabling increased extracellular PGRN levels through inhibition of sortilin-mediated PGRN degradation. Here we report the development of a high-affinity sortilin-binding affibody-peptide fusion construct capable of increasing extracellular PGRN levels in vitro. By genetic fusion of a sortilin-binding affibody generated through phage display and a peptide derived from the progranulin C-terminus, an affinity protein (A3-PGRNC15*) with 185-pM affinity for sortilin was obtained. Treating PGRN-secreting and sortilin-expressing human glioblastoma U-251 cells with the fusion protein increased extracellular PGRN levels up to 2.5-fold, with an EC50 value of 1.3 nM. Our results introduce A3-PGRNC15* as a promising new agent with therapeutic potential for the treatment of frontotemporal dementia. Furthermore, the work highlights means to increase binding affinity through synergistic contribution from two orthogonal polypeptide units.